2014
DOI: 10.17576/jkmjc-2014-30si-01
|View full text |Cite
|
Sign up to set email alerts
|

The Past and Coming Communication Journey in Malaysia

Abstract: The paper recorded the tremendous changes in the academic and media landscape in tracing the development of communication studies since its beginning in 1971. Universiti Sains Malaysia (USM) was the first to offer the communication programme followed by Universiti Technology MARA (UiTM), Universiti Kebangsaan Malaysia (UKM) and the other public universities. USM and UiTM benefitted from the American experts in the preparation of their academic programmes. The early communication programmes in public universiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Other articles reviewed did not mention a specific approach, failing to demonstrate methodological rigour. The findings concur with Hassan and Salleh (1990) and Idid's (2014) scholarly work on communication trends indicating that quantitative research were the most frequently employed. The same sentiment can be seen in the trends analyses of the Western scholars, where Zhang and Leung (2014) stated that quantitative approaches were more dominant in social networking sites studies (75%) from the year 2006 until 2011.…”
Section: Developmental Phases Of Researchsupporting
confidence: 88%
See 3 more Smart Citations
“…Other articles reviewed did not mention a specific approach, failing to demonstrate methodological rigour. The findings concur with Hassan and Salleh (1990) and Idid's (2014) scholarly work on communication trends indicating that quantitative research were the most frequently employed. The same sentiment can be seen in the trends analyses of the Western scholars, where Zhang and Leung (2014) stated that quantitative approaches were more dominant in social networking sites studies (75%) from the year 2006 until 2011.…”
Section: Developmental Phases Of Researchsupporting
confidence: 88%
“…This result contradicts with previous literature of theoretical trends. In Malaysia, past studies revealed that Malaysian scholars were lacking in conceptualising or applying theories in research (Hassan & Salleh, 1990;Merican, 2005;Idid, 2014). In addition, research trends analyses in the Western countries illustrated that communication and social media related research are atheoretical with approximately 15-40% of the articles presented an explicit theory or theoretical framework (Kamhawi & Weaver, 2003;Bryant 7 Miron, 2004;Cho & Khang, 2006;Khang, Ki & Ye, 2012).…”
Section: Developmental Phases Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…They also organised campaigns to educate people on the voting process (Bashir, n.d). Due to the rise of nationalism and series of political, social and economic growth, there was a strong need for personnel and trained professionals in the field of public relations (Idid, 2014).…”
Section: Introductionmentioning
confidence: 99%